Venous thromboembolism in patients with COVID-19 and correlation with D-dimers: a single-centre experience. Issue 1 (16th November 2020) - Khan, Muhammad Ziaullah; Jamal, Yousaf; Sutton, Benjamin; Rauf, Farrukh
Abstract : Objective: To study the frequency of venous thromboembolism in hospitalised patients with COVID-19 and correlation with the D-dimers and thromboprophylaxis. Design: Cross-sectional descriptive study. Place and duration of study: Queen Elizabeth Hospital, 20 April 2020–13 May 2020. Patients and methods: One hundred and seven (n=107) patients of PCR-confirmed COVID-19 pneumonia admitted to Queen Elizabeth Hospital, Birmingham, between 20 April 2020 and 13 May 2020 were included in the study using consecutive sampling. Data were collected using the Excel audit tool and included age, gender, weight, estimated eGFR, D-dimer values on admission, intensive care unit admission, presence of respiratory failure, imaging results for evaluation of venous thromboembolism (VTE) and anticoagulation received on admission. The data were entered in the SPSS (V.17) and were analysed. Data were summarised as means±SD, number or percentage as appropriate. A p value of less than 0.05 was considered significant. Results: The frequency of VTE was found to be 11.2% in patients hospitalised with COVID-19 pneumonia. The mean D-dimers were 3322.24 ng/mL±9603 ng/mL with the values significantly higher for patients with VTE and those requiring intensive care unit admission. All of the seven patients (100%) with D-dimers value above 2000 ng/mL who underwent imaging were found to have VTE. Conclusion: VTE is frequent in patients with COVID-19 pneumonia despite anticoagulation. A higher D-dimers value correlates well with the risk of VTE in these patients and further evaluation of such patients for VTE is necessary especially with D-dimers values above 2000 ng/mL.